2020
DOI: 10.1587/transinf.2019ini0001
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Secret Key Generation Scheme Based on Wireless Channel Characteristics for 5G Networks

Abstract: Secret key generation based on channel characteristics is an effective physical-layer security method for 5G wireless networks. The issues of how to ensure the high key generation rate and correlation of the secret key under active attack are needed to be addressed. In this paper, a new practical secret key generation scheme with high rate and correlation is proposed. In our proposed scheme, Alice and Bob transmit independent random sequences instead of known training sequences or probing signals; neither Alic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Recently, researchers found that CSI can counter this attack because it can extract channel information from different subcarriers and attacker's movement has different impact on different subcarriers [72,136]. To counter predictable channel attack for RSSI-based key generation system, researchers have proposed a variety of methods by introducing different kinds of randomness into the channels, such as using multiple attennas [104], rotating attenna [127], transmitting random signals [128], and other schemes [15,32,34,43,77].…”
Section: Predictable Channel Attackmentioning
confidence: 99%
“…Recently, researchers found that CSI can counter this attack because it can extract channel information from different subcarriers and attacker's movement has different impact on different subcarriers [72,136]. To counter predictable channel attack for RSSI-based key generation system, researchers have proposed a variety of methods by introducing different kinds of randomness into the channels, such as using multiple attennas [104], rotating attenna [127], transmitting random signals [128], and other schemes [15,32,34,43,77].…”
Section: Predictable Channel Attackmentioning
confidence: 99%